Dietary Acid Load (DAL), Glycated Hemoglobin A1c (HbA1c), and Metabolic Syndrome (MeS) Mediate the Association of the Adherence to the Dietary Approaches to Stopping Hypertension (DASH) and Mediterranean Diet (MeD) With Nonalcoholic Fatty Liver Disease - Doustmohammadian, Azam; Nouri Saeidlou, Sakineh; Esfandyari, Saeed; Gholizadeh, Esmaeel; Maadi, Mansooreh; Motamed, Nima; Ajdarkosh, Hossein; Khoonsari, Mahmoodreza; Clark, Cain C. T.; Zamani, Farhad (Frontiers in Nutrition, 2022)
The study aimed to investigate the association of dietary approaches to stop hypertension (DASH) and Mediterranean Diet (MeD) with nonalcoholic fatty liver disease (NAFLD), using structural equation modeling (SEM), among Iranian adults. In this population-based cross-sectional study, 3220 adults (44.65% female), aged ≥18 years, were selected from the Amol Cohort Study (AmolCS). The dietary intakes were assessed by a validated 168-item semi-quantitative food-frequency questionnaire (FFQ). Residual method energy adjustment of MeD and DASH scores were calculated. Demographic characteristics and anthropometric and laboratory measurements were collected. NAFLD was diagnosed by an expert radiologist via ultrasound sonography. Based on the primary hypothesis, DASH, MeD, and NAFLD were fitted in models. Metabolic syndrome (MetS) as a potential risk factor directly affected NAFLD in all these models. In both genders, adherence to DASH negatively affected NAFLD indirectly through the two following paths. 1) Dietary acid load (DAL) and metabolic syndrome 2) DAL and HBA1c. In addition, DAL positively affected NAFLD among male participants indirectly via HBA1c and MeS. Similarly, in both genders, the relationship between MeD and NAFLD was mediated through 1) DAL, HBA1c, and MeS and 2) DAL and MeS. Further, among male participants, the MeD and NAFLD were also associated via the mediators of HBA1c and MeS. In female participants, adherence to MeD directly influenced NAFLD. The present study found three important mediators, including DAL, HBA1c, and MeS, in the association of DASH and MeD with NAFLD. Preventive and therapeutic interventions should target the mediators, including DAL, HBA1c, MeS, and its components, to reduce NAFLD incidence in the general population.